Analysis of the Effect of Stock Split and Dividend Policy on the Stock Liquidity of Go Public Companies - Umar Sumardi; Nizwan Zukhri; Rini Yayuk Priyati (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2022)
The purpose of this study is to analyze the effect of the stock split and dividend policy by the company on the liquidity of the shares of companies listed on the Indonesia Stock Exchange. This study used an event study design, where observations were made 10 days before and 10 days after the event. The population contained in the study are companies that carry out Stock Split and Dividend policies for the 2017-2021 period. Data analysis in this study is the Shapiro Wilk test and the Wilcoxon Signed Ranks Test. This study found that stock split policy has no effect on stock liquidity. Dividend policy has no effect on stock liquidity.